Evaluation of ACI 318-19 and EC2 on moment redistribution of post-tensioned continuous beams with steel tendons - Lee, Lucas Guan Yin (Nanyang Technological University, 2021)
This study is focused on the topic of moment redistribution in post-tensioned continuous beams with steel tendons, specifically in two-span symmetrically loaded beams. It is known that prestressed reinforced concrete beams are able to achieve a higher slenderness ratio and durability as compared to their normal reinforced concrete counterparts. However, there are uncertainties in the understanding of moment redistribution in prestressed concrete beams as compared to reinforced concrete beams. An extensive investigation into the factors influencing moment redistribution through numerical models using DIANA was carried out in this study to provide more clarity. Although the ACI 318-19 code provision was developed based on net tensile strain, while the EC2 provision was developed based on a neutral axis depth, both ACI 318-19 and EC2 have provided their respective provisions for moment redistribution in prestressed concrete beams as that for reinforced concrete beams. The applicability of ACI 318-19 and EC2 code provision have been included in this study. The investigation has revealed that parameters not considered in the provisions of ACI 318-19 and EC2, such as eccentricities of prestressed tendons, load condition, slenderness ratio, ps and pp, influences moment redistribution. Particularly, eccentricities of prestressed tendons and load conditions are significant considerations. ACI 318-19 was found to be more rational than EC2 when used to evaluate the degree of moment redistribution in these post-tensioned beams.